CtDNA release mechanisms in a therapeutic Ewing Sarcoma mouse model - Eiblwieser, Johanna; Krumbholz, Manuela; Semper, S.; Frey, Benjamin; Nagel, L.; Bäuerle, Tobias; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08

Quantification of translocation-specific ctDNA provides an integrating parameter for early assessment of treatment response and risk stratification in ewing sarcoma - Krumbholz, Manuela; Eiblwieser, Johanna; Ranft, Andreas; Zierk, Jakob; Schmidkonz, Christian; Stuetz, Adrian M.; Peneder, Peter; Tomazou, Eleni M.; Agaimy, Abbas; Bäuerle, Tobias; Hartmann, Wolfgang; Dirksen, Uta; et al. (Clinical Cancer Research, 2021)
Purpose: We evaluated the predictive and prognostic value of circulating tumor DNA (ctDNA) in patients with Ewing sarcoma (EWS) treated in the EWING2008 trial. Experimental Design: Plasma samples from 102 patients with EWS enrolled in the EWING2008 trial were obtained before and during induction chemotherapy. Genomic EWSR1 fusion sequence spanning primers and probes were used for highly specific and sensitive quantification of the levels of ctDNA by digital droplet PCR. ctDNA levels were correlated to established clinical risk factors and outcome parameters. Results: Pretreatment ctDNA copy numbers were correlated with event-free and overall survival. The reduction in ctDNA levels below the detection limit was observed in most cases after only two blocks of vincristine, ifosfamide, doxorubicin, and etoposide (VIDE) induction chemotherapy. The persistence of ctDNA after two VIDE blocks was a strong predictor of poor outcomes. ctDNA levels correlated well with most established clinical risk factors; an inverse correlation was found only for the histologic response to induction therapy. ctDNA levels did not provide simple representations of tumor volume, but integrated information from various tumor characteristics represented an independent EWS tumor marker with predictive and prognostic value. Conclusions: ctDNA copy number in the plasma of patients with EWS is a quantifiable parameter for early risk stratification and can be used as a dynamic noninvasive biomarker for early prediction of treatment response and outcome of patients.
CRIS-Team Scopus Importer:2021-11-26